Clinical and Pathological Findings in Green Turtles (Chelonia mydas) from Gladstone, Queensland: Investigations of a Stranding Epidemic - Flint, Mark; Eden, Paul A; Limpus, Colin J; Owen, Helen; Gaus, Caroline; Mills, Paul C (EcoHealth, 2015)
An investigation into the health of green turtles was undertaken near Gladstone, Queensland, in response to a dramatic increase in stranding numbers in the first half of 2011. A total of 56 live turtles were subject to clinical examination and blood sampling for routine blood profiles, and 12 deceased turtles underwent a thorough necropsy examination. This population of green turtles was found to be in poor body condition and a range of infectious and non-infectious conditions were identified in the unhealthy turtles, including hepato-renal insufficiency (up to 81%, 27/33 based on clinical pathology), cachexia (92%, 11/12), parasitism (75%, 9/12), cardiopulmonary anomalies (42%, 5/12), gastroenteritis (25%, 3/12), masses (25%, 3/12) and mechanical impediments (17%, 2/12 based on necropsy). Overall, there was no evidence to indicate a unifying disease as a primary cause of the mass mortality. Recent adverse weather events, historic regional contamination and nearby industrial activities are discussed as potential causative factors.